The Durability of Concrete Wall Panel Containing Bamboo Mat as Reinforcement Material - Lee, Yie Jie; Mohd Noh, Hamidun (Research in Management of Technology and Business, 2022)
Reinforced concrete wall panel has widely used in the commercial and residential building. However, there have some problems arise when the use of reinforcement steel bar in concrete wall panel contributes to carbon emission to environment, depletion of natural resource, the corrosion of steel bar and the increase in the cost of steel bar. On the other hand, bamboo is suitable to be use as reinforcement material in concrete wall panel because the maximum load-bearing capacity of treated bamboo reinforcement is closely equivalent to steel reinforcement. Besides, bamboo is abundant resources in Malaysia where there are about 421,722 hectare of bamboo area in peninsular Malaysia. In this research, bamboo was used as the reinforcement material due to its strength and availability in Malaysia. The research objective for this research are to compare the compressive strength between bamboo reinforced concrete wall panel and standard concrete wall panel, to determine the durability of bamboo reinforced concrete wall panel and to observe the feedback of bamboo mat as reinforcement material among construction stakeholders. The compressive strength of specimens with dimension of 300 mm x 300 mm x 150 mm is tested according to ASTM C805-97. Moreover, the durability test has carried out in accordance with ASTM C 267-01 which the specimen is soak in the 10% sulphuric acid solution for 7 days. Meanwhile, qualitative method has conducted through interview to achieve third objective. Experimental results of this research are there is a comparable compressive strength between two type of specimens which there is only 5.9 MPa (18%) different between the compressive strength of both type of specimens and the bamboo reinforced concrete wall panel are acceptable when exposed in normal environment. From qualitative analysis, all respondents are agreed with bamboo mat as reinforcement material must be tested and approve by legal expert before it is implemented. This study is aimed to reduce the use of steel bar in construction which can lead to the sustainable building construction and enhance the economy by using bamboo mat as reinforcement material in concrete.